Language Planning and Microlinguistics
XIV, 243 p.
Keywords: Whilst earlier studies of language planning and of standardisation have tended to study macro processes, this volume is in line with more recent work aimed at bridging the macro and the micro levels by examining how the two interact and influence each other. It covers seven countries and deals with a range of sociolinguistic constellations.